159 Effect of ionophore, implant, and beta-adrenergic agonists on key indicators of sustainable beef production. (30th November 2020) - Baber, Jessica; Sawyer, Jason T; Holland, Ben; Karr, Kendall; Word, Alyssa; Wickersham, Tryon
Abstract: Net protein contribution (NPC) of the beef value chain has been evaluated and it has been demonstrated that the beef value chain positively contributes to NPC; however, the specific role of growth-enhancing technologies has not be evaluated. To compare effects of technology on NPC baseline, performance data from 8 commercial feedlots located in the Texas panhandle (n = 6) and Kansas (n = 2) were used to create 8 scenarios: 1) no technology (NT), 2) ionophore (ION), 3) implant (IMP), 4) beta-agonist (B), 5) ionophore and implant (ION+IMP), 6) ionophore and beta-agonist (ION+B), 7) implant and beta-agonist (IMP+B), and 8) ionophore, implant and beta-agonist (I+I+B). An IMP×B interaction was observed for human-edible protein conversion efficiency (HePCE) and NPC (P ≤ 0.03). Implants and beta-agonists increased HePCE and NPC compared to NT (P < 0.01), and IMP+B was greater than combined effects of IMP and B. Ionophore scenarios had greater HePCE and NPC compared to NT (P < 0.01). Interactions for ION×IMP and IMP×B were observed for NPC of beef value chain (P < 0.03), but an ION×B interaction was not observed (P = 0.07). All technology scenarios were lower than NT for NPC (3.21 vs 3.74, respectively; P < 0.01) because HePCE for the beef value chain was reduced when cattle were fed longer in the technology scenarios. Interactions for ION×IMP, IMP×B, and ION×B were observed for enteric CH4 production feedlot cattle (P ≤ 0.03), and a three-way interaction was observed for enteric CH4 production of the beef value chain (P < 0.01). All technologies reduced enteric CH4 produced per kg of HePg compared to NT (P < 0.01). Net protein contribution should be balanced with other indicators of sustainability for a representative understanding of technology impacts on sustainable beef production.